PENGARUH PENERAPAN PENDEKATAN PEMBELAJARAN BERBASIS KEMAMPUAN OTAK (BRAIN BASED LEARNING) TERHADAP KEMAMPUAN APRESIASI CERITA PENDEK - Tita Adiz Pradani Cahyaniastuti; Kusmiyati Kusmiyati; Nuril Huda (Klitika: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
One reason for the low ability to appreciate short stories students is the lack of media that is able to connect students to be able to like short story appreciation lessons. This can cause students to feel bored to participate in learning and have an impact on the low value of Indonesian. One effort to overcome this is to use innovative learning models to develop skills in students, namely the brain based learning model. The purpose of this study is to find out whether or not there is an effect of the brain based learning model on the ability to appreciate short stories in class XI students of Islamic Parlaungan Waru Sidoarjo. The population in this study were students of class XI Islamic High School Parlaungan Waru 2018/2019 school year as many as 62 students. By using a total sampling technique or the overall sample which is divided into 2 sample groups, namely class XI IPA totaling 30 students as an experimental class using a brain based learning model and class XI IPS totaling 32 students as a control class using conventional learning models. Analysis of the data of this study used the t-test. Based on the results of data analysis and hypothesis testing, it is concluded that there is a change in the brain based learning model towards the ability to appreciate short stories in class XI students of Islamic Parlaungan Waru High School. This is shown from the results of testing the hypothesis by t-test using SPSS 16 software, obtained tcount = 3.123> ttable 2,000. From the test results also known the average value of the experimental class post-test of 88.00 while the average value of the post-test of the control class was 82.25 which means that the experimental class taught using the brain-based learning model has a higher value than the class controls that are taught using conventional learning models